Optimization ZnO Properties for Electron Transport Layer (ETL) of Hybrid Solar-cell Prepared with Sol-gel Method Combined with Reflux Treatment - Pardi Sampe Tola (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2022)
Electron-hole pair (exciton) generation and extraction from solar-cell photoactive layer is the main parameters determined solar-cell performance. Generally solar-cell consists of a photoactive layer sandwiched between electron transport layer (ETL) and hole transport layer (HTL). Exciton separation and extraction from photoactive layer depend on several properties: energy level match of photoactive layer and charge transport layer, surface contact area of photoactive layer and charge transport layer, and charge transport properties of charge transport layer. ETL and HTL should meet several characteristic e.g.: high transparency in UV-visible light region, high degree of crystallization to minimize charge lose and high electron or hole mobility. In this study we try to fabricate ZnO as an ETL of hybrid solar-cell with sol-gel method combined with reflux treatment. The quality of ZnO ETL highly effected by precursor solution properties; solution homogeneity, viscosity and stability. These precursor solution properties depend on chemical composition and reaction condition, reflux treatment designed to enhance precursor solution reaction time and increase solution stability. Previous study shown low solution stability of ZnO precursor prepared with sol-gel without reflux treatment which resulting on low ETL quality. Visible observation of the resulting precursor solution showed that reflux treatment enhances solution stability, while solution prepared without reflux treatment easily formed precipitation phase. Furthermore, ZnO powder prepared with reflux treatment exhibit preferable crystallization and small ZnO crystallite size. Low-temperature crystallization of ZnO prepared with sol-gel method combined with reflux treatment, make it is possible to fabricate thin film with small particle size therefore able to enhance surface contact area of photoactive layer and ETL.